Les invisibles des futuristes - Costanza Bertolotti (Images Re-Vues)
Futurist painters have since 1910 declared that their art could allow the perception of invisible and fleeting forces, using a suggestive rather than a mimetic language. In order to understand what these force are and where this claim stems from, beyond referring to the Futurists’ interest for occultism, one has to take into account the part played, in the development of Futurist painting, by social experiences of modernity, among which the crowd is the most striking. Despite the traditional image showing an Avant-Garde devoted to the idol of speed, the analysis reveals a yet unseen face of Futurism, marked by the dialectics between modernity and magical survivals.